Puts in the Shadow - Singh, Manmohan (IMF Working Papers; Working Paper ;, 2012)
In the aftermath of the Lehman crisis, payouts (i.e., taxpayer bailouts) in various forms were provided by governments to a variety of financial institutions and markets that were outside the regulatory perimeter - the a"shadow" banking system. Although recent regulatory proposals attempt to reduce these a"puts", we provide examples from non-banking activities within a bank, money market funds, Triparty repo, OTC derivatives market, collateral with central banks, and issuance of floating rate notes et cetera, that these risks remain. We suggest that a regulatory environment where puts are not ambiguous will likely lower the cost of bail-outs after a crisis.